Green human resource management and corporate social responsibility: Evidence from Brazilian firms. Issue 4 (2nd April 2020) - Freitas, Wesley Ricardo de Souza; Caldeira-Oliveira, Jorge Henrique; Teixeira, Adriano Alves; Stefanelli, Nelson Oliveira; Teixeira, Talita Borges
Abstract : Purpose: In the past, simply fulfilling economic performance alone was critical to ensuring the success of companies and their shareholders, but this traditional perspective is not compatible with society's current demands, as there is increasing social pressure on organizations to become more sustainable and reduce impacts on the environment, promoting sustainable results in their business processes. In this context, the specialized literature states that human resources management (HRM) is considered a central aspect for building sustainable organizations, in particular, the area of green human resources management (GHRM). Thus, this study analyzes the relationship between GHRM and corporate social responsibility (CSR) in Brazilian companies. Company's age, size, ISO 9001 and 14001 certifications are the control variables. Design/methodology/approach: The authors adopted a quantitative approach in conducting the survey. Four waves of email were sent to HR and CSR managers from 853 Brazilian companies from the metallurgical, automotive and chemical industries. In total, 79 questionnaires were fully answered, higher than the minimum sample calculated by the G *Power 3.1 software, which corresponds to a return rate of 9.26%. For the analysis of the results, the partial least squares method was used. Findings: This research identifies that GHRM practices, in fact, positively influence CSR practices. The findings evidence that practices of performance evaluation, teamwork and recruitment and selection are the most important for a better CSR performance. The research results indicate that the "ISO 9001 certification" control variable also has a positive and significant effect on CSR and that the size of the company, the age of the company and the ISO 14001 certification, in the analyzed sample, were not relevant (as control variables) for CSR. Originality/value: Current literature highlights the gap between GHRM and CSR. This relationship is not explored in Brazil. The study uses a new theoretical model, and it fills the gap identified in the literature. This paper brings important theoretical and managerial contributions. It is the first in the literature to show, in an empirical way, the positive relationship between GHRM and CSR, contributing in an original way to the state of the art of the GHRM and CSR theme. In addition, this research adds empirical evidence on GHRM and CSR in Latin America/South America/Brazil.